Monogenic diabetes prevalence among Polish children—Summary of 11 years‐long nationwide genetic screening program. Issue 1 (24th April 2017) - Małachowska, Beata; Borowiec, Maciej; Antosik, Karolina; Michalak, Arkadiusz; Baranowska‐Jaźwiecka, Anna; Deja, Grażyna; Jarosz‐Chobot, Przemysława; Brandt, Agnieszka; Myśliwiec, Małgorzata; Stelmach, Małgorzata; Nazim, Joanna; Peczyńska, Jadwiga; et al.
Abstract : Background: Estimated monogenic diabetes (MD) prevalence increases as screening programs proceeds. Objective: To estimate prevalence of MD among Polish children. Subjects: Patients and their family members suspected of suffering from MD (defined as causative mutation in one of the Maturity Onset Diabetes of the Young or permanent neonatal diabetes mellitus genes) were recruited between January 2005 and December 2015. Methods: Nationwide prevalence was estimated based on data from 6 administrative provinces (out of 16 in Poland) with high referral rates of patients (>10 per 100 000 children). Results: During the analysis, probands from 322 of 788 screened families tested positive yielding a total of 409 children and 299 family members with MD. An average of 70 probands/year were referred. Screening success rate reached 40% over the study period. We estimated the prevalence of MD in 2015 to 7.52/100 000 children (1 in 13 000). The most frequent MODY in this group was GCK‐ MODY (6.88/100 000). The prevalence estimates increased nearly 2‐fold since our report in 2011 (4.4/100 000). However, the figure reached a plateau because of screening saturation in 2014 what was also proven by lowering of the median age of diagnosis lowered in time ( R = −0.73, P = .0172) along with shortening of the delay between clinical and genetic diagnosis ( R = −0.65, P = .0417). Conclusions: The screening for childhood MD in Poland reached a plateau phase after 10 years showing a stable prevalence estimate. The true frequency of MD in the overall population may be higher given later onset of reportedly more frequent types of MD than GCK ‐MODY.